Cover Image, Volume 233, Number 3, March 2018. Issue 3 (29th November 2018) - Ghasabi, Mehri; Mansoori, Behzad; Mohammadi, Ali; Duijf, Pascal HG; Shomali, Navid; Shirafkan, Naghmeh; Mokhtarzadeh, Ahad; Baradaran, Behzad
Abstract : Cover : The cover image is based on the Review Article MicroRNAs in cancer drug resistance: Basic evidence and clinical applications by Mehri Ghasabi et al., DOI: 10.1002/jcp.26810 .